Cloning of Litopenaeus vannamei CD63 and it's role in white spot syndrome virus infection. (July 2016) - Guan, Guang-Kuo; Liu, Qing-Hui; Li, Chen; Huang, Jie
Abstract: White Spot Syndrome Virus (WSSV) is currently the most serious shrimp pathogen, which has brought huge losses to shrimp industry worldwide. CD63 of shrimp belongs to the tetraspanin superfamily, which plays an important role in signal transduction and immune process. In this paper, CD63 cDNA sequence of Litopenaeus vannamei was cloned using RACE method. The amplified sequence is 1472 bp, with its ORF 744 bp, encoding 247 amino acids. Bioinformatics analysis showed that the sequence of LvCD63 has 93% similarity with Penaeus monodon and 92% similarity with Fenneropenaeus chinensis . Real-time PCR analysis showed that the mRNA levels of LvCD63 expressed in the tissues of hemocytes, gill, epithelial tissue, heart, lymphoid, hepatopancreas, stomach, intestines, muscle and nerve. Among these tissues the highest expression level was showed in the tissue of haemolymph, followed by epithelial tissue, hepatopancreas, and nerve. The lowest expression level of LvCD63 was appeared in the muscle tissue. After WSSV challenge, the expression levels of LvCD63 were both up-regulated in the tissues of gill and epithelial. However the expression level of LvCD63 in hepatopancreas was down-regulated. Far-western blot analysis showed that LvCD63 interacts with VP28, and both VP28N and VP28C fragments interact with LvCD63. Flow cytometry analysis showed that LvCD63 was present on the surface of hemocytes and it is required for binding of WSSV virions. Neutral experiments in vivo showed that LvCD63LEL delayed WSSV infection in shrimp. Graphical abstract: Highlights: The expression levels of LvCD63 were both up-regulated in the tissues of gill and epithelial, and had a down-regulated in hepatopancreas. LvCD63 can interact with VP28, and both VP28N and VP28C fragments can interact with LvCD63. LvCD63 had a distribution in the surface of hemocytes and required for binding of WSSV virions. LvCD63 LEL delayed shrimp from WSSV infection.